Product Design and Development of the Incashback Application Using an Operations Management Approach - Amaris, Nadia (Integrative Perspectives of Social and Science Journal, 2026)
1"}The rapid growth of digital technology has encouraged businesses to develop innovative digital platforms that can improve operational efficiency and provide additional value to users. This study aims to analyze the design and development process of the Incashback application using an operations management approach. The research adopts a qualitative case study method, with primary data collected through semi-structured interviews with the business owner of Incashback. The findings show that the idea for developing the application emerged from observing the increasing number of digital transactions in everyday activities such as online shopping, bill payments, and other digital services. The development process involved collaboration between managerial and technical teams to determine the key features of the platform, particularly the cashback distribution mechanism. However, the development stage also revealed several operational challenges, including system automation and operational efficiency. The study concludes that successful digital product development requires the integration of market opportunity analysis, iterative feature development, and effective operations management to ensure that the application can deliver value to users and operate sustainably in a competitive digital environme